FINITE ELEMENT MODELING IN IRREGULAR SHELL COMPONENT OF AUTOMOTIVE DRIVELINE - WANG Liang; HU Fang; CHEN LiQing; CHEN WuWei (Jixie qiangdu, 2016)
The problem of inaccurate results was presented based on irregular shell finite element analysis using traditional modeling methods,a finite element modeling method was presented based on simplified of transmission components. The paper introduced the bearings,gears and fasteners of simplified model method. For example,finite element analysis of automobile main reducer shell based on finite element software environment. Two finite element analysis models were established based on traditional method and simplify component method; Comparing simulation results of the two models found: stress distribution on the overall trend of automobile main reducer Shell was the same,but the value of the local area to install the bearing stress positions were quite different. Stress tests show in 100 N. m,200 N. m and 400 N. m of input torque main reducer: Simplified model approach closer to actual value of test results,verify the correctness and accuracy of the method.